The Sensitivity of the Regression Parameters - Esager, Marwa (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
Theory of statistics and its application to data analysis in all fields of endeavor, forms the base of statistical analysis. While data collection and validation is not dealt with in this thesis, the importance of data on the analysis results is obvious. In general data are discrete observations in a continuous process. Number of variables involved is also very important. Hence, multivariate statistical analysis has gained importance, especially after computers could be used to process huge amounts of data. In this thesis, simple and multivariate regression techniques, principal component analysis are explained in detail, and also used in the analysis of a real life data. Since the matrix algebra is implemented in all computations, a brief introduction to certain concepts of matrix algebra is also given under Chapter 3. Chapter 4 introduces some important concepts of multivariate linear regression theory, while Chapter 5 gives basic theoretical background to principal component analysis. In the application section a data set consisting of 8 variables affecting the heating load of buildings is studied. Following careful examination of the variables and pairwise correlations, it was considered useful to reduce the number of variables to 5, all having a high correlation with the dependent variable. An attempt is made to estimate the predictor variables after the principal components were obtained. The methodology used proved to be a successful one as estimation errors were minimal.

ÖZ: İstatistik teorisi ve her alandaki veri analizine olan uygulaması istatistiğin temelini oluşturur. Veri toplanması, temizlenmesi veya geçerliliğnin saptanması bu tezin kapsamına alınmadı. Ancak verilerin istatistik analizi ve analiz sonuçları üzerindeki etkisi ortadadır. Veriler sürekli bir olayın ayrık ölçümlerinden elde edilen değerlerdir. Bu nedenle çok deişkenli istatistiksel analiz gittikçe önem kazanmakta ve özellikle bilgsayar yazılımlarının istatistik analizindeki kullanımı bu önemi dahada artırmaktadır. Bu tezde basit ve çok değişkenli regresyon teknikleri, temel bileşenler analizi detaylı olarak açıklanmıştır. Teorik kısmın uygulaması çok değişkenli gerçek bir veri üzerinde yapılmıştır. Tüm uygulamalarda matris cebiri teorilerinden yararlanıldığı için, matris cebiri ile ilgili bazı temel kavramlar kısaca açıklanmıştır. Dördüncü kısımda çok değişkenli lineer regresyon teorisi ile ilgili kavramlar, beşinci kısımda ise temel bileşenler analizi konusunda bazı temel teorik detaylar verilmiştir. Uygulama alanında ise binaların ısı yüklenme kapasitelerini etkileyen 8 değişkenli bir işlemden elde edilen veriler incelenmiştir. Değişkenlerin titiz incelenmesi sonucunda ısı yükleme kapasinde en etkin olan 5 değişkenin analiz işlminde kullanılmasına karar verilmiştir. Elde edilen temel bileşenler kullanılarak etkin olduğu varsayılan 5 değişkenin tahmini yapılmıştır. Tahmin sonuçlarının geçerli olduğu tahmin hatalarının küçüklüğü ile kanıtlanmıştır.
Master of Science in Mathematics. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Mathematics, 2018. Supervisor: Assist. Prof. Dr. Yücel Tandoğdu.
Keywords: Mathematics; Statistical Mathematics; Matrix algebra; regression analysis; estimation; predictors; response; regression coefficients; principal components analysis; eigenvector; eigenvalue